2021
DOI: 10.1590/s0102-0536-20210111
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of tomato rootstocks to Ralstonia solanacearum and R. pseudosolanacearum in Mata mesoregion, PE

Abstract: Bacterial wilt limits tomato production and resistant rootstocks could be important for the integrated management of the disease. Since there is an interaction between local bacterial strains and tomato genotype, this study aimed to evaluate 14 tomato rootstocks to bacterial wilt in the Mata mesoregion of Pernambuco state, Brazil. The rootstocks reaction to two sequevars of Ralstonia solanacearum and two of R. pseudosolanacearum was evaluated in four experiments carried out in the greenhouse using the complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…To get a better estimate of the diversity of potential hosts for Ralstonia, we did a search of the literature using search terms like "weeds", "host range", and older names for the pathogen (Pseudomonas solanacearum, Burkholderia solanacearum). [189][190][191][192][193] 2022 [194][195][196][197][198] Converting strain metadata into a structured format for data science:…”
Section: Article Selection Criteria and Search Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…To get a better estimate of the diversity of potential hosts for Ralstonia, we did a search of the literature using search terms like "weeds", "host range", and older names for the pathogen (Pseudomonas solanacearum, Burkholderia solanacearum). [189][190][191][192][193] 2022 [194][195][196][197][198] Converting strain metadata into a structured format for data science:…”
Section: Article Selection Criteria and Search Strategymentioning
confidence: 99%
“…B Note that sequevar is an imperfect phylogenetic system. See Sharma et al 2022 for details [189] Extracting metadata for genomes available on NCBI.…”
Section: Databasementioning
confidence: 99%
“…Summary of the analysis of variance (mean square values) for the variables in interval between the 15th and 20th day of evaluation Cultivars, there were signi cant differences at 1% probability by the F test for all variables, except for INC, because the variance was zero, since all plants had 100% incidence of bacterial wilt Albuquerque et al (2021),. in Chã Grande/PE under greenhouse conditions at 34º C, observed that the cultivars Hawaii 7996 and Yoshimatsu obtained incidences of 53.12% and 87.50% respectively.…”
mentioning
confidence: 98%
“…In group two are the cultivars Santa Adélia, Bartô and Coração de Boi with 48.62%, 51.04% and 56.25% bacterial wilt respectively. In the third group are the cultivars Yoshimatsu, Hawaii 7996, Cereja, IPA-7, Santa Clara 5.800 and Santa Cruz Kada Gigante, with a range of 66.67% − 77% of index bacterial wilt.In a study conducted byAlbuquerque et al (2021) evaluating the cultivars Hawaii 7996 and Yoshimatsu as rootstocks under greenhouse conditions in relation to R. pseudosolanacearum, with the isolate CRMRs126, they obtained an average disease rate of 37.5% and 81.87%, respectively, in Chã Grande/PE with an average temperature of 34° C and relative humidity of 65%. In this same experiment, with the inoculation of another isolate of R. pseudosolanacearum, CRMRs116, Hawaii 7996 and Yoshimatsu obtained lower disease rates, on average 10.62% and 40%, respectively.…”
mentioning
confidence: 99%